Лазер на парах бромида меди с высокой частотой следования импульсов; Квантовая Электроника; Т. 32, № 8 - Шиянов Д. В. Дмитрий Валерьевич; Евтушенко Г. С. Геннадий Сергеевич; Суханов В. Б. Виктор Борисович; Федоров В. Ф. (2002, 2002)
Заглавие с экрана